Comparative numerical simulation of inhaled particle dispersion in upper human airway to analyse intersubject differences. Issue 6 (July 2020) - Phuong, Nguyen Lu; Khoa, Nguyen Dang; Ito, Kazuhide
This study predicted the total and regional deposition of particles in realistic upper human airways and demonstrated the effects of intersubject variations in deposition fraction. Two airway models were studied under flow rates ranging from 0.45 to 2.4 m 3 /h and particle aerodynamic diameters from 1 to 10 μm. The total deposition predictions were validated using in vivo and in vitro experimental data. The intricate airway structures generated heterogeneities of airflow distributions and corresponding particle dispersions and depositions in the models. Nevertheless, with modified inertial parameters, the total deposition fraction curves of the two human upper airway models, as functions of flow rates, converged to a single function. However, regional particle deposition fractions differed significantly among the two models. The surface pressure and wall-shear stress distribution were investigated to assess the relationship of surface pressure and wall-shear stress with hotspot locations in upper airways of both models. For one subject (model A), the central nasal passage regions were found to be sites of higher deposition over the range of particle sizes and flow rates targeted in this study. For the other subject (model B), higher deposition was mostly observed in the vestibule region, caused due to particle inertia as the airway consisted of curvatures. The accelerated flow regions acted as a natural filter to high inertial particles. The results indicated that both total and regional depositions exhibited significant intersubject differences.